Synergistic visible-light photocatalysis by ZnO/black phosphorus nanohybrids immobilized on activated kaolinite - Ngue Song, Pierre; Lambert, Stéphanie D.; Farcy, Antoine; Ouhaibi, Abdelhalim; Lejeune, Louise; Eloy, Pierre; Hermans, Sophie; Delaey, Maxime; Poelman, Dirk; Mahy, Julien G. (Next materials, 2026)
This study reports the design and synthesis of a novel composite photocatalyst based on ZnO nanoparticles immobilized onto a black phosphorus (BP)-modified activated kaolinite matrix. The fabrication strategy combines solvothermal doping and sol-gel methods to achieve a hybrid 2D/3D semiconductor system. Comprehensive characterization, including XRD, XPS, UV-Vis DRS, PL, SEM, and TEM, confirmed the successful integration of ZnO and BP within the clay structure. The resulting composites exhibited enhanced photocatalytic activity under visible light compared to pure ZnO, as evaluated by the degradation of two polyazo dyes (Direct Red 80 and Chicago Sky Blue 6B). The Activated Clay/BP/ZnO composite showed superior performance, with first-order kinetic constants up to three times higher than those of pure ZnO. This improvement is attributed to improved charge separation, defect engineering, and strong interfacial interactions within the heterostructure. These findings highlight the potential of BP-doped clay-supported ZnO composites as efficient, sustainable photocatalysts for wastewater treatment. [Display omitted] •A novel AC/BP/ZnO heterostructure was synthesized via solvothermal and sol–gel methods.•ZnO nanoparticles were immobilized onto BP-doped activated kaolinite from Cameroon.•The composite exhibited superior visible-light photocatalytic activity for azo dye removal.•Photoluminescence and zeta potential measurements had confirmed enhanced charge separation.•A degradation mechanism involving interfacial synergies was proposed and validated.